2007
DOI: 10.1083/jcb.200612046
|View full text |Cite
|
Sign up to set email alerts
|

The disintegrin and metalloproteinase ADAM12 contributes to TGF-β signaling through interaction with the type II receptor

Abstract: Transforming growth factor-β (TGF-β) regulates a wide variety of biological processes through two types of Ser/Thr transmembrane receptors: the TGF-β type I receptor and the TGF-β type II receptor (TβRII). Upon ligand binding, TGF-β type I receptor activated by TβRII propagates signals to Smad proteins, which mediate the activation of TGF-β target genes. In this study, we identify ADAM12 (a disintegrin and metalloproteinase 12) as a component of the TGF-β signaling pathway that acts through association with Tβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 26 publications
6
106
0
Order By: Relevance
“…npg TGF-β receptors are dynamically distributed on the plasma membrane [10]. Interleukin-6 [43], ADAM12 [44] and cholesterol depletion [45] can partition TβRI from the lipid raft microdomains into non-lipid raft regions, while hyaluronan [46] and the polysaccharide heparin sulfate [47] promote lipid raft localization of TβRI. Several lines of evidence showed that caveolin, which is enriched in lipid rafts, is required for TβRI turnover [38,46,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…npg TGF-β receptors are dynamically distributed on the plasma membrane [10]. Interleukin-6 [43], ADAM12 [44] and cholesterol depletion [45] can partition TβRI from the lipid raft microdomains into non-lipid raft regions, while hyaluronan [46] and the polysaccharide heparin sulfate [47] promote lipid raft localization of TβRI. Several lines of evidence showed that caveolin, which is enriched in lipid rafts, is required for TβRI turnover [38,46,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In activated hepatic stellate cells, TGF-βl induces ADAM-12 expression which might also participate in tumour progression [139]. It is worth pointing out that a recent study identified ADAM-12 as a partner of TGFβ receptor II signalling where it stabilizes the TGFβ RII protein and potentiates Smad-mediated signalling [140]. Hence, ADAM-12 might contribute to growth inhibitory signalling in normal epithelial cells which is lost during tumour progression.…”
Section: Liver Carcinomamentioning
confidence: 99%
“…ADAM12 (a disintegrin and metalloproteinase 12) is a glycoprotein with zinc protease and integrin-binding activities in its extracellular domain and has been implicated in the control of membrane fusion, cytokine and growth factor shedding, and cell migration [98]. A recent study reported that it can interact with the extracellular domain of TbRII and enhance TGF-b signaling [99]. Interestingly, neither its protease activity nor the intracellular domain is required for this stimulatory effect.…”
Section: Turnoff Of Tgf-β Signaling In Lipid Rafts/caveolaementioning
confidence: 99%